Potensi Vitamin D3 pada Minyak Ikan Lambak Pipih untuk Penurunan Sitokin Pro Inflamasi - Sakdiah, Siti; Sitanggang, Fardiah Tilawati; Maharani, Eva Ayu; Widhyasih, Retno Martini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the differences in vitamin D3 levels in fish oil in the body parts of lamb fish. The method used is an experiment with a Factorial Randomized Design with three replications. The results showed that the Vitamin D3 content in lamb fish oil is quite high, ranging from 767.52 IU / g to 787.34 IU / g. The highest vitamin D3 content is in group one, namely the whole fish (scales, head, meat, bones, and innards). The conclusion is that there is a significant difference between the vitamin D3 content in fish oil and whole fish, meat, meat, and waste. Keywords: Inflammation, Fish Oil, Flat Lambak, Vitamin D